(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
The growing consciousness among consumers of the importance of health has resulted in the mushrooming of various nutraceutical products in the market. This rapid growth has created the opportunity for nutraceuticals manufacturers to take advantage of producing and marketing those products via contract manufacturing. Contract manufacturing allows anyone to own a product with minimum capital without the need to have certain expertise or even adequate knowledge or skills concerning the science behind the nutraceutical products. The issue that arises is the absence of proper regulations that control the production of nutraceutical products. In Malaysia, nutraceuticals can be regulated by different regulatory agencies depending on their classification. This creates a double standard as different agencies have different standard procedures that govern the product. This paper analyses the issue pertaining to the development of nutraceutical products through contract manufacturing, and seeks to propose that there is a real need to have a specific, standard procedure to safeguard and protect consumer interest in the long run. The study was conducted through content analysis of various literatures, as well as focus group discussions with relevant authorities. Keywords: Nutraceuticals, product, contract manufacturing, regulatory bodies